Immortalization of primary marmoset skin fibroblasts by CRISPR-Cas9-mediated gene targeting - Yeon-Ju Jeong; Jeongin Cho; Jina Kwak; Young Hoon Sung; Byeong-Cheol Kang (Animal Cells and Systems, 2022)
ABSTRACTImmortalized cell lines can be used for diverse in vitro experiments, providing invaluable data before conducting in vivo studies Callithrix jacchus, the common marmoset, is a non-human primate model utilized for studying various human diseases. However, only a few immortalized marmoset cell lines are currently available. In the present study, we reveal that CRISPR-Cas9-mediated targeting of the p53 gene or CDKN2A locus is an effective means for immortalizing primary marmoset skin fibroblasts. In addition to frameshift mutations that result in premature stop codons, in-frame mutations potentially destroying the DNA-binding motif of p53 are frequently detected in immortalized cells. Like Cdkn2a-deficient mouse cells, CDKN2A-deficient marmoset cells express wild-type p53 proteins normally respond to genotoxic stresses, including adriamycin and etoposide. Taken together, these findings indicate that Cas9- mediated gene targeting of the p53 gene or CDKN2A locus is an effective tool for establishing immortalized marmoset cell lines with defined genetic alterations.